The impact of diet in early life on adipose tissue growth and development in sheep - Birtwistle, Mark D.A. (2016)
Adipose tissue is found in two main forms: white (WAT), which stores energy; and brown (BAT), which dissipates energy as heat by means of a unique mitochondrial protein, UCP1. In large mammals, BAT is rapidly replaced by WAT after birth, but it has recently been found that functional BAT is present in human adults, which raises the possibility that it could be manipulated to burn off excess fat. The main aim of this thesis was to investigate, using sheep as a model, the effect of early nutritional interventions on fat mass and on the expression in adipose tissue of genes involved in adipogenesis, metabolism, thermogenesis and development. A secondary aim was to study their ontogeny in sternal adipose tissue.